1987
DOI: 10.1139/v87-322
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized replicates of sequence 136–148 of human serum albumin as adsorbents for bilirubin

Abstract: . Can. J. Chem. 65, 1927Chem. 65, (1987. Strategic peptide sequences, patterned on the sequence 136-148 of the primary structure of human serum albumin, have been immobilized on a cross-linked polyacrylamide support using the solid phase peptide synthesis technique. Certain of the resulting materials proved to be efficient adsorbents for bilirubin from aqueous phosphate buffer solution. Amino acids such as lysine and arginine favour the binding of the ligand, whereas glutamic acid reduces it markedly. From S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1988
1988
1993
1993

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…Previous reports from this laboratory have demonstrated that certain peptides immobilized on a cross-linked polymer support form efficient adsorbents for bilirubin (6)(7)(8). This paper describes the adsorption behaviour of adsorbents with pendants synthesized from amino acids, such as lysine and arginine, that have been shown previously to be of key importance for the adsorption of bilirubin (6)(7)(8) and have been reported to be involved in the binding of bilirubin by HSA (9-1 1).…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…Previous reports from this laboratory have demonstrated that certain peptides immobilized on a cross-linked polymer support form efficient adsorbents for bilirubin (6)(7)(8). This paper describes the adsorption behaviour of adsorbents with pendants synthesized from amino acids, such as lysine and arginine, that have been shown previously to be of key importance for the adsorption of bilirubin (6)(7)(8) and have been reported to be involved in the binding of bilirubin by HSA (9-1 1).…”
Section: Introductionmentioning
confidence: 95%
“…Peptide resins were hydrolyzed at 110°C for 48 h according to previously published procedures (8). Amino acid analyses were performed using a Varian 5500 Analyzer.…”
Section: Amino Acid Analysesmentioning
confidence: 99%
See 3 more Smart Citations